Unveiling the counselling experiences of spiritual hypnotherapy with Islamic approach among female child victims of incest - Low, Sofiyyah Siew Ping (2022)
Child abuse is an all-inclusive disorder. Young victims of incest tend to experience greater trauma than the victims of other forms of sexual abuse. In Malaysia, the topic of Child Sexual Abuse (CSA) has received very little research attention. Consequently, very few clinical interventions exist for CSA victims. Likewise, very few studies had explored the experiences of children who had undergone therapy for CSA. Given the general prevalence of religion and spirituality, more research is needed on the potential of spiritual hypnosis as a treatment for CSA victims, particularly in Malaysia. To date, no study has been conducted on spiritual hypnosis therapy for CSA victims, particularly those that incorporate an Islamic approach. To address the aforementioned gap, this study poses two main research questions (RQ): 1) How to perform an appropriate Spiritual Hypnotherapy with Islamic Approach (SPHIA) procedure for abuse victims? and 2) What do participants experience during the SPHIA procedure, specifically through i) seeing, ii) listening, and iii) feeling? This study incorporates two theoretical perspectives in the model development namely: 1) hypnotherapy, and 2) spirituality in addition to the Islamic healing model. These two theories guided the model design, and the exploration and generation of new data related to the phenomenon as derived from the participants’ experiences. A qualitative phenomenological research design was used to unveil the experiences of six female children, aged between 13 and 18, who were victims of incest via the usage of SPHIA. This study employed the inductive approach. Firstly, data was collected through participant observation and in-depth interview in the Malay language to investigate the participants’ experiences while undergoing SPHIA. Each videotaped and recorded interview, which lasted between 45 to 60 minutes, was transcribed verbatim and analysed using the Nvivo 12 Plus software. Ethics of confidentiality were well addressed. The trustworthiness of the study was ensured through the triangulation of the participant observations, in-depth interviews, and documentation analysis. The outcome answered RQ 1 which aims to explicate the process of developing the SPHIA model via eight sessions namely: i) building rapport, ii) conducting semi-structured interviews and questionnaire, iii) exploring the participants’ spirituality, iv) education sessions about hypnotherapy, v) conducting SPHIA using Script 1 and Script 2, and vi) conducting in-depth interviews using Script 1 and Script 2. In-depth examination of the RQs 2 unveiled three themes of experiences through seeing namely people, comforting scenery, and projected objectives of their future. The three themes of experiences through listening are the anchoring, making wishes to Allah, and conversation with religious idol. Lastly, the three themes of experiences through feeling are the conscious feeling of being hypnotized, feeling of being highly charged emotionally, and the feeling of transcendence. SPHIA is a counselling intervention that enhances the participants’ hypnotic, religious and spiritual experiences. Spiritual evolvement in hypnotherapy can restructure and reframe the mental imagery in the unconscious mind and effectively help participants heal during the psychotherapeutic process. SPHIA is considered a potential intervention for this target group (CSA) in KSKCareCentre, and future studies on its effectiveness are recommended.